2013
DOI: 10.1007/s00464-013-2787-9
|View full text |Cite
|
Sign up to set email alerts
|

The value of percutaneous ultrasound in predicting conversion from laparoscopic to open cholecystectomy due to acute cholecystitis

Abstract: BackgroundLaparoscopic cholecystectomy has become the treatment of choice for gallstone disease. Advantages of the laparoscopic approach include lower morbidity and mortality rates, reduced length of hospital stay, and earlier return to work. In acute cholecystitis, severe inflammation makes laparoscopic dissection technically more demanding, with a higher risk of related complications that require conversion to open cholecystectomy.MethodsWe reviewed the records of 5,596 patients who underwent cholecystectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 27 publications
1
41
0
2
Order By: Relevance
“…The risk of CTO doubles with every millimetre increase in gallbladder wall thickness (OR = 2; 95% CI: 1.7-2.3; P < 0.001) [52]. Patients with GB wall thickness >5 mm on transabdominal US have a 16 times higher risk of CTO than those with GB wall thickness 3-5 mm (OR = 16.3; 95% CI: 8.1-33.3; P < 0.00005) [35]. GB wall thickness >4 mm on US is not only a radiological marker for AC but also associated with greater operational difficulty [40,61].…”
Section: Risk Factors and Predictivementioning
confidence: 99%
See 2 more Smart Citations
“…The risk of CTO doubles with every millimetre increase in gallbladder wall thickness (OR = 2; 95% CI: 1.7-2.3; P < 0.001) [52]. Patients with GB wall thickness >5 mm on transabdominal US have a 16 times higher risk of CTO than those with GB wall thickness 3-5 mm (OR = 16.3; 95% CI: 8.1-33.3; P < 0.00005) [35]. GB wall thickness >4 mm on US is not only a radiological marker for AC but also associated with greater operational difficulty [40,61].…”
Section: Risk Factors and Predictivementioning
confidence: 99%
“…Diagnostic criteria for AC are presented in Table 2 [34]. AC patients have eight times higher risk of CTO than patients with uncomplicated gallstone disease (OR = 8.01; 95% CI: 6.1-10.5; P < 0.00005) [35]. Severity grades of AC, as defined by the 2013 Tokyo Guidelines, are associated with an increased rate of CTO [36,37].…”
Section: Preoperative Patient-related Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslam HMet al (2013) described the relative importance of clinical, [11] biochemical and ultrasonographic parameters in preoperative assessment for GB surgery. Cwik G et al (2013) found that many USG factors were more common in OC group vs LC group. [12] Out of these, presence of exudates around GB, suboptimal visualization of the pericholecystic anatomy on and GB wall thickening of >5 mm were significant predictors of OC.…”
Section: Discussionmentioning
confidence: 95%
“…Cwik G et al (2013) found that many USG factors were more common in OC group vs LC group. [12] Out of these, presence of exudates around GB, suboptimal visualization of the pericholecystic anatomy on and GB wall thickening of >5 mm were significant predictors of OC. Pinto Aet al (2013) & Melamud Ket al (2014) studied significant predictors of OC.…”
Section: Discussionmentioning
confidence: 95%